Recruitment and consent of adults with intellectual disabilities in a classic grounded theory research study: ethical and methodological considerations. Issue 2 (7th February 2017) - Carey, Eileen; Griffiths, Colin
Abstract: Researchers are required to provide opportunities for people with intellectual disabilities to be included in research which affects their lives. This paper reports on one research study inclusive of 12 adults with intellectual disabilities. Ethical and methodological realities of recruiting research participants and obtaining informed consent while enlisting a classic grounded theory methodology are discussed. The findings of this paper focus on building and maintaining trusting relationships with relevant gatekeepers and engaging in reasonable accommodations to support decision-making for and with adults with intellectual disabilities. This paper contributes to an understanding of how to apply for ethical approval, negotiate access to potential participants, enlist reasonable accommodations and obtain informed consent in the context of the methodological strictures of classic grounded theory methodology. Research projects need to be carefully planned making space for the development of empathic relationships with both the potential participants and also with the structures and services supports.